Technical writing for dummies - Lindsell-Roberts, Sheryl (--For dummies., 2023)
Learn to document the technology that makes the world go Technical Writing For Dummies is a master class on how to build a career writing user manuals, e-learning, streaming, simulations, and more. It even zooms into the metaverse. Whether you're new to the field, a seasoned professional, or a technical person who needs to write, this guide arms you with the skills you need to cash in on this flourishing world of technical writing. This isn't your average how-to. It's a compendium of innovative industry knowledge that will help you set yourself apart with the latest trends and best practices in technical writing. As a tech writer, you'll need a robust skillset that allows you to offer clear and concise documentation for just about anything. This new edition of Technical Writing For Dummies--updated for all of today's tech writing advances--can get you there. Uncover the basics of technical writing and master common documentation types Get insight into the career paths available to tech writers today Discover new remote collaboration options and cloud-based tools for technical writers Learn how to elevate your documents for high search engine optimization (SEO) rankings Improve your craft to connect with diverse, global audiencesWhether you're a technical writer or technical professional who needs to write--you can learn the best practices of effective technical writing, as well as how to navigate its various formats and platforms, thanks to this handy Dummies guide.